La comunicación institucional y el fortalecimiento de la imagen corporativa del gobierno autónomo descentralizado del cantón Sigchos - Artos Tipanluisa, Lourdes Mercedes (2016)
This poses the creation of a Communication Plan for the Decentralized Autonomous Government of the Sigchos canton, of the province of Cotopaxi. The Institutional communication and corporate image, its background, origins, theories and analyzes administrative functions, social responsibilities, according to the Organic Code of territorial organization of autonomous decentralized. In order to improve communication mechanisms between the internal and external public of the municipality, also it defines social, cultural and administrative elements of the institution; which is part of its structural organization. Analyze the situation of the internal and external communication of the institution through surveys and interviews. It concludes with the development of strategies to improve communication between employees and the citizens of Sigchos Canton.